Mao zhuxi wuxian xinren Hua zhuxi, quanguo renmin relie yonghu Hua zhuxi - Liu Renqing,
'Chairman Mao had a boundless trust in Chairman Hua, all the people enthusiastically support Chairman Hua.' Printno. 8071.236.